The Impact Autonomous Maintenance on Operational Performance: An Analytical Study at the Baghdad Soft Drinks Company - Amer Abdul Latif Kadhum; Salem Bader Mohammad; Omar Amer Hamed (Journal of Techniques)
This research aims to investigate the impact of autonomous maintenance on operational performance dimensions that focuses on cost, quality, delivery, and flexibility.  The research sample has targeted the departments of production operations namely; production, maintenance, projects, and quality in the Baghdad Company for Soft Drinks. Data collected by using a survey questionnaire. In total (86) staff were invited to practice in this survey. There are (81) forms that were valid for statistical analysis. Quantitative statistical methods were used for the purpose of data analysis using the (SPSS V.24) program such as; Cronbach's alpha test, kurtosis and skewness, arithmetic mean, standard deviation, coefficient of variation, Spearman's correlation coefficient, coefficient of determination and impact factor. conclusions, The most important conclusions reached by this research are that autonomous maintenance has a strong statistically significant effect on the dimensions of operational performance, especially cost, quality, delivery, and flexibility.